Cytological study on Dumortiera hirsuta (Sw.) Nees (Hepaticae) - Loo, M.J; Monica Suleiman; Mariam Abd. Latip (Sabah Forestry Department, 2005)
The cytological approach was used in this study on Dumortiera hirsuta (Sw.) Nees (Class Hepaticae) because its cytoforms are complex and morphologically not distinct. Chromosome numbers, ploidy levels and lengths of chromosomes of D. hirsuta were determined. It was observed that there were three levels of ploidy in D. hirsuta: monoploid with chromosome numbers of n = 9, diploid with n =18, and triploid with n = 27. The mean length of chromosomes in monoploid cytoform was 1.20 pm and longer than that of the diploid cytoform (1.12 pm) and triploid cytoform (1.10 pm). The karyological approach had successfully differentiated cytoforms at the cellular level.